Traces of Ambon Bananas from Banyuwangi to Western Australia (1914–1930) - Alifia Noor Octaviany (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This study examines the export of Ambon bananas from Banyuwangi to Western Australia during the period 1914–1930 as part of the dynamics of colonial horticultural trade. The research is motivated by the limited historical scholarship on fruit exports compared to major plantation commodities such as sugar, coffee, and rubber. It aims to explain the background of banana export development in Banyuwangi, the process of its establishment and expansion, and the factors influencing its growth and fluctuations. This study employs the historical method proposed by Gilbert J. Garraghan, consisting of heuristics, source criticism, synthesis, and exposition. Primary sources include Vruchtenhandel en-cultuur in Nederlandsch-Indie (1931), the Jaarboek van het Departement van Landbouw, Nijverheid en Handel in Nederlandsch-Indie, and reports of the colonial government pomologist. The findings reveal that the success of Banyuwangi's banana exports was supported by its strategic geographical location, colonial government policies through the distribution of superior seedlings, cultivation guidance, quality control, and increasing demand from the Australian market. Nevertheless, export development fluctuated due to the First World War, quarantine regulations, plant diseases, and Australian protectionist policies. From the perspective of Theotonio Dos Santos' Dependency Theory, Banyuwangi functioned as a peripheral production region whose export performance depended heavily on the economic policies and market dynamics of Australia, demonstrating the structural dependency that characterized colonial trade relations.